Practical aspects of cross-training (IAAF @-Letter for CECS Level II Coaches, 2004)
It appears that some transfer of training effects on VO2max exist from one mode to another. The training effect seems to be more noticeable when running is performed as a cross-training mode. Swim training, on the other hand, may result in minimum transfer of training effects on VO2max for other activities. Cross-training effects never exceed those induced by a specific training. The principles of specificity of training tend to have greater significance, especially for highly trained athletes. But even for these athletes cross-training may be an appropriate supplement during rehabilitation periods from physical injury or when suffering from mental distress (Tanaka, 1994, p. 337).